2012
DOI: 10.1155/2012/859219
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Family-Based Association Analysis of Seven Candidate Polymorphisms with Essential Hypertension in an African-Derived Semi-Isolated Brazilian Population

Abstract: Background. It has been widely suggested that analyses considering multilocus effects would be crucial to characterize the relationship between gene variability and essential hypertension (EH). Objective. To test for the presence of multilocus effects between/among seven polymorphisms (six genes) on blood pressure-related traits in African-derived semi-isolated Brazilian populations (quilombos). Methods. Analyses were carried out using a family-based design in a sample of 652 participants (97 families). Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
2
25
0
9
Order By: Relevance
“…A total of six studies [23][24][25][26][27][28][29] were found. Of these, one [29] did not met our eligibility criteria (i.e.…”
Section: Characteristics Of the Participant Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of six studies [23][24][25][26][27][28][29] were found. Of these, one [29] did not met our eligibility criteria (i.e.…”
Section: Characteristics Of the Participant Studiesmentioning
confidence: 99%
“…The G-350A promoter variant Four investigations encompassing 7,292 participants (2,738 hypertensives and 4,554 normotensives; 3,550 overweight and 3,742 lean) were available for the association of the G-350A promoter variant with both blood pressure-and adiposity-related phenotypes [23,26,28,30]. All controls groups were in Hardy-Weinberg equilibrium (Supplementary Tables S1-S2).…”
Section: Single-marker-based Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations